Strengthening National Vision and National Defense for PSHT Warrior Candidates Ranting Saradan Madiun - Moch. Ichdah Asyarin Hayau Lailin; A. Taufiq; Eko Sutrisno (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
The younger generation faces various national challenges in the digital era, such as the spread of hoaxes, intolerance, and a decline in the spirit of nationalism. Prospective warriors of the Setia Hati Terate Brotherhood (PSHT) as part of the youth community have a strategic role in instilling national values and defending the country. A national education program is needed that is able to increase the understanding and character of nationality effectively. Community service activities were carried out using a participatory national education approach involving 127 prospective PSHT Ranting Saradan warriors from 133 registered participants. The methods used include interactive lectures, group discussions, case studies, and joint reflection. The effectiveness of the program was evaluated through pre-test and post-test using 15 indicators that included aspects of Pancasila, the 1945 Constitution, the Republic of Indonesia, Bhinneka Tunggal Ika, defending the country, and contemporary national challenges. The results of the evaluation showed that the average level of participants' understanding increased from 68.3% in the pre-test to 89.0% in the post-test or an increase of 20.7 points. The highest increase occurred in the understanding of the concept of national defense, the form of national defense for the younger generation, and the impact of hoaxes on national unity. The participatory national education program has proven to be effective in improving national insight and the character of defending the country for prospective PSHT Ranting Saradan warriors. A participatory approach that integrates national values with the organizational culture of pencak silat has the potential to become a model of community service that can be replicated in other youth communities.